2023
DOI: 10.1088/1402-4896/accc14
|View full text |Cite
|
Sign up to set email alerts
|

Hole transport through an isotype amorphous-crystalline Ge2Sb2Te5 heterojunction under forward bias

Abstract: The transport of holes through a representative isotype amorphous-crystalline Ge2Sb2Te5 heterojunction under forward bias is explored for the first time. An approximate analytic model, based on the exact solution to Poisson’s Equation, the Continuity Equation, and the Transport Equation, is proposed to describe the forward current-voltage characteristic and hole quasi-Fermi level distribution across the heterojunction with a reduced set of material and device parameters. The proposed model incorporates thermio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…In addition to the drops in E Fn across the c-GST and a-GST layers, E Fn drops also across the c-GST contact and across the a-GST/c-GST interface, though they are not apparent in figure 7. While this indicates thermionic emission across E V respectively, as well as the hole quasi-Fermi level distribution, E Fp (x) [5], are also indicated. The inset magnifies the drop in E Fn (x) across the c-GST layer at 0.15 V. these interfaces, the negligible drops demonstrate that transport across these interfaces does not limit electron transport through the device at either bias.…”
Section: Simulation Results and Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In addition to the drops in E Fn across the c-GST and a-GST layers, E Fn drops also across the c-GST contact and across the a-GST/c-GST interface, though they are not apparent in figure 7. While this indicates thermionic emission across E V respectively, as well as the hole quasi-Fermi level distribution, E Fp (x) [5], are also indicated. The inset magnifies the drop in E Fn (x) across the c-GST layer at 0.15 V. these interfaces, the negligible drops demonstrate that transport across these interfaces does not limit electron transport through the device at either bias.…”
Section: Simulation Results and Discussionmentioning
confidence: 96%
“…By resolving the drift and diffusion components of J e (x), represented by the orange and purple curves in figures 6(a) and (b) respectively, it is found that electron transport through the bulk of the c-GST layer is predominantly diffusive at either applied bias whereas electron transport through the bulk of the a-GST layer is diffusive at low biases (0.15 V) but mixed at larger biases (0.40 V). The reason for the superior contribution of the drift component in this case is the electric field induced within the a-GST QNR by the significant hole current density which passes through the heterojunction at larger applied bias [5].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations